EXECUTION OF TAX DELINQUENT ASSETS AGAINST MORTGAGE RIGHTS AT STATE-OWNED ENTERPRISE BANKS - Samuel Maraja Agung; Syamsul Bachri; Achmad Ruslan (Awang Long Law Review, 2022)
This paper aims to analyze the legal aspects of the execution of tax arrears assets that have been tied to Mortgages in State-Owned Banks. This type of research is normative legal research using a statutory approach and a conceptual approach. Primary legal materials, secondary legal materials, and tertiary legal materials were obtained through library studies and supplemented by interviews. The collected legal materials are then analyzed qualitatively. The results showed that the tax office has the right to receive prepayment for the execution of the taxpayer's property due to a tax debt. State-owned banks also have the right to receive repayments first compared to other creditors for the execution of mortgage objects, as a result of default by the debtor. In this case, the Tax Office and the State-Owned Bank both have the right to receive payment first compared to other parties. Based on the applicable regulations, there is no article that specifically and in detail regulates which payment should be prioritized if the Tax Office and State-Owned Bank both have an interest in the execution of the same object for the settlement of tax debts and debts to creditors. Therefore, it is necessary to coordination between the Tax Office and State-Owned Banks to obtain solutions in solving problems, with consequences that are not detrimental to the Tax Office and State-Owned Banks.